Relationship Between Leadership Ostracism and Employee Engagement: A Moderated Mediation Model - Joko Suyono,; Lilik Wahyudi,; Harmadi,; Risgiyanti,; Suryandari Istiqomah, (Asian Academy of Management Journal, 2024)
This study investigated the effect of leadership ostracism on employee engagement through defensive silence as a mediating variable, using the conservation of resources theory framework and the need-threat/need fortification model. The study also examined the role of external social support, which has the potential to moderate the indirect effect of leadership ostracism on employee engagement. Data were collected from civil servants in Indonesia using self-report questionnaires. Using the snowball sampling technique, an online survey was conducted to collect data. Of 504 accepted responses, 310 met all the criteria and were analysed using partial least square-structural equation modelling (PLS-SEM) and a moderated mediation model. The moderated mediation analysis showed that low perceived external social support indirectly strengthens the negative influence of leadership ostracism on employee engagement through defensive silence. This research enriches the ostracism literature, especially regarding leadership ostracism and its relationship with employee engagement, which has not been empirically tested in previous studies.